Diklat Pembuatan Karya Tulis Ilmiah Berorientasi Pembelajaran Berdiferensiasi bagi Guru Kabupaten Kubu Raya - Bistari, Bistari; Dashela, Tarina; Yuliastuti, Indah; Wahyuni, Renni Dwi; Nurhasanah, Nurhasanah; Asmawarni, Asmawarni; Daniarti, Daniarti; Nursanti, Ria (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
This training adapts to the needs of teachers in the independent curriculum. The Education Office in collaboration with FKIP Tanjungpura University trained 70 teachers in Kubu Raya district, focusing on differentiated learning. Participants were reinforced on the characteristics and types of differentiated learning: proactive, emphasizing quality, rooted in assessment, and providing multiple approaches. They are directed to choose or combine differentiated learning types (content, process, product) and link them to research such as PTK, best practice, or descriptive papers. Participants submit a draft paper with title and background for the resource person to comment on. Implementation in schools is monitored via WhatsApp by the Kesuma Bangsa Journal team. The purpose of implementation is as a real action for driving teachers and article material for journals. The activity was closed with a post-test to assess the increase in understanding, which increased from 45.07 to 56.07 points. The training went smoothly and according to plan.